Eco-friendly and efficient extraction of phenolic compounds from Commiphora gileadensis bark using microwave-assisted extraction - Aiman A., Mokaizh; Nour, Abdurahman Hamid; Ali, Gomaa A.M.; Ukaegbu, Chinonso Ishmael; Hawege, Emsalem Faraj (Elsevier, 2024)
Commiphora gileadensis (C. gileadensis) is a medicinal plant with a variety of biological activity; its bark has several therapeutic potentials, including the treatment of wounds, inflammatory diseases, and treating bacterial infections. This study utilized microwave-assisted extraction (MAE) to optimize the recovery and phenolic components of the ethanolic extracts of C. gileadensis bark. Different MAE process parameters (microwave power, irradiation time, sample/solvent ratio, extraction temperature, and solvent (ethanol) concentration) were studied for their impacts on the extraction process using One-Factor-At-a-Time (OFAT) method. The extracts were further characterized for the presence of different phytochemicals using Gas Chromatography-Mass Spectroscopy (FC-MS) and Fourier Transform Infrared Spectroscopy (FTIR) analyses. The experimental findings revealed that the maximum extraction yield, total phenolic content (TPC), and total flavonoid content (TFC) of the ethanolic extract of the of C. gileadensis bark using MAE process were 39.40 ± 0.47 w/w%, 166.41 ± 3.97 mg GAE/g d.w., and 52.83 ± 2.95 mg QE/g d.w., respectively. Furthermore, 30 phenolic constituents were discovered in the extract of C. gileadensis bark for the first time, and these compounds showed good in vitro antioxidant activity. Hence, MAE is a suitable technique for efficient and green extraction of different groups of phytochemicals of pharmaceutical importance from the bark of C. gileadensis.